Studi Usaha Perikanan di Kawasan Terumbu Pulau Sagori Sulawesi Tenggara - Afyudi, Bobby; Fahrudin, Achmad; Susanto, Handoko Adi (Jurnal Aplikasi Manajemen, 2016)
Abstract: Sagori island waters is rich of coral reef and reef fish with high economic value. It's has also been designated as a general use zone by the government. In the other side, the needs of consumption is increasing by the growth of people in the Island and neighbours as well. Those condition, presumed as the main factor for fisherman to increase their effort in catching the reef fishes, in any possible way. However, Visual Census technique (VCT) shows that that the number of reef fish was spread evenly on a coral reef condition is still good enough, but are not in a reverse condition. That is then presumed as the static production value of coral reef ecosystem (SPV). The economic value of coral reefs per hectare in Sagori Islands is shown based on Present Value Generated per Hectare (PV) which state that people in Sagori Island has just use about 56.99% of the resources. By cash flow analysis within projected to 10 years ahead, this fisheries business unit shows that it is still good to be performed.